Water Oxidation: Tunable Electrodeposition of Ni Electrocatalysts onto Si Microwires Array for Photoelectrochemical Water Oxidation (Part. Part. Syst. Charact. 1/2018). (23rd January 2018) - Tung, Ching‐Wei; Chuang, Yen; Chen, Hsiao‐Chien; Chan, Ting‐Shan; Li, Jiun‐Yun; Chen, Hao Ming
Abstract : Isolated nickel nanoparticles are decorated on n‐type silicon microwire arrays by tunable electrodeposition technique, which offers an excellent photocurrent performance for PEC water oxidation by Prof. Hao Ming Chen and co‐workers in article No.1700321 . The electrodeposition technique of nickel electrocatalysts onto the silicon microwire arrays enables the active species with precise control of elemental composition, which can place the surface catalysts at the locations where the charge carries are most feasible for PEC reaction. The optimizing photoanode shows a maximum photocurrent density of ∼35 mA cm −2 and retains ∼90% of initial current density for several hours. This work affords a guide for designing the geometry of absorber surface and electrocatalyst, in which the photocurrent responses can be optimized by tuning dispersity and size of nickel electrocatalysts. This study opens up a new horizon for pursuing solar energy conversion and artificial photosynthesis, paving the way for future practical applications.